Working of the monetary system in India - Pathak, Dattuprasad Shankarlal, 1939- (Dept. of Business Economics, Faculty of Commerce, M.S. University of Baroda : copies can be had of University Publications Sales Unit, 1979)
An analytic structure for the determination of money stock and money income in India during 1951-1966.